2019
DOI: 10.1007/s00259-019-04287-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the PET-CT score for diagnosis of malignant pleural effusion

Abstract: Purpose Although some parameters of positron emission tomography with 18 F-fluorodeoxyglucose ( 18 F-FDG) and computed tomography (PET-CT) are somehow helpful in differentiating malignant pleural effusion (MPE) from benign effusions, no individual parameter offers sufficient evidence for its implementation in the clinical practice. The aim of this study was to establish the diagnostic accuracy of a scoring system based on PET-CT (the PET-CT sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
0
27
0
2
Order By: Relevance
“…Yang et al. [23] established a scoring system based on five PET-CT parameters for the differential diagnosis of MPE and BPE, and the sensitivity and specificity in the derivation cohort were 83.3% and 92.2%, respectively, with a cutoff value of 4. In addition, Porcel et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al. [23] established a scoring system based on five PET-CT parameters for the differential diagnosis of MPE and BPE, and the sensitivity and specificity in the derivation cohort were 83.3% and 92.2%, respectively, with a cutoff value of 4. In addition, Porcel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no specific method for differentiating MPE from BPE is perfect in clinical settings. Yang et al [23] established a scoring system based on five PET-CT parameters for the differential diagnosis of MPE and BPE, and the sensitivity and specificity in the derivation cohort were 83.3% and 92.2%, respectively, with a cutoff value of 4. In addition, Porcel et al [24] constructed a CT scan-based scoring system, and this scoring model achieved a sensitivity of 88% and a specificity of 94% with a cutoff value of 7 points in the validation set.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study [ 11 ] demonstrated that combination of four indexes (age, proteins, glucose, and lactic acid) selected by logistical regression to separate tuberculous pleurisy from BPE achieved 78% specificity and 93.5% sensitivity with an area under curve (AUC) of 0.915. Yang et al [ 12 ] exploited logistic model to develop a PET-CT scoring model for the differential diagnosis of MPE and BPE, and the scoring model yielded a sensitivity of 83.3% and a specificity of 92.2% with the cut-off value of 4 points in the training group. Hence, the predictive performances of diagnostic models created by logistical regression are somewhat limited.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, medical thoracoscopy is considered as a highly sensitive (92.7%) method for diagnosing pleural effusions (3,14). This year, our group found that the PET-CT score can be an efficient method to diagnose MPE, with an area under the curve of 0.949 (15). However, both medical thoracoscopy and PET-CT require high technology support and have a high cost.…”
Section: Introductionmentioning
confidence: 99%